COVID-19 online medical education and outcomes on Internal Medicine In-Training Examination scores. Issue 3 (4th May 2023) - Fan, Jerry; Metting, Austin
Abstract: Background: COVID-19 presented a unique opportunity to explore new methods to deliver medical education virtually due to requirements for social distancing. We provided webcams and microphones in each of our core teaching team rooms. We used existing teleconferencing systems with share screen, polling, and audio/video capabilities to continue fostering a group learning environment. Methods: The Internal Medicine In-Training Examination (IM-ITE) was used as a surrogate measurement of the effectiveness of virtual medical education, comparing composite scores from 2015 to 2019 (pre-COVID, in-person conference) to 2020 (post-COVID, virtual conference) for each postgraduate class. Results: No statistically significant differences between the mean or median scores on the IM-ITE were noted for all three classes. Conclusion: Although COVID-19 presented many challenges to residency programs across the United States, our pilot study demonstrated that virtual medical education did not result in lower IM-ITE scores and may be an innovative solution to bridge the education gap during COVID-19.